Effect of Tube Diameter on the Design of Heat Exchanger in Solar Drying system - Abdulmalek, S.H. (Institute of Physics Publishing, 2018)
The drying of agriculture product consumes a huge fossil fuel rates that demand to find an alternative source of sustainable environmental friendly energy such as solar energy. This work presents the difference between using solar heat source and electrical heater in terms of design aspect. A circular-finned tube bank heat exchanger is considered against an electrical heater used as a heat generator to regenerate silica gel in solar assisted desiccant drying system. The impact of tube diameter on the heat transfer area was investigated for both the heat exchanger and the electrical heater. The fin performance was investigated by determining fin effectiveness and fin efficiency. A mathematical model was developed using MATLAB to describe the forced convection heat transfer between hot water supplied by evacuated solar collector with 70 Â°C and ambient air flow over heat exchanger finned tubes. The results revealed that the increasing of tube diameter augments the heat transfer area of both heat exchanger and electrical heater. The highest of fin efficiency was around 0.745 and the lowest was around 0.687 while the fin effectiveness was found to be around 0.998. Â© Published under licence by IOP Publishing Ltd.